2011
DOI: 10.1071/sh10059
|View full text |Cite
|
Sign up to set email alerts
|

The importance of striving for greater efficiency

Abstract: Abstract. Health care costs are rising faster than inflation in almost all developed countries. Improving the efficiency of health care will go some way to address this issue. There has been a significant improvement in the delivery of sexual health care with a particular focus on innovation. In this issue, Baraitser et al. evaluate their services, that uses computer-assisted interviewing combined with self-collected samples in London. This editorial discusses this service in the context of the control of sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The provision of a risk quiz to the IWTK home collection programme was added to encourage participants to take a look at their own risk for having an STI, perhaps with gaining knowledge as to their own risk. Self-management of one's own reproductive health is becoming more popular; and improvement in the efficiency and delivery of sexual health care with a focus on innovation may popularise ‘Do it yourself’ sexual healthcare 17. Baraitser et al 18 have reported on the user experience for patients collecting their own samples, reporting that “clients were grateful for the service and preferred the autonomy, privacy and speed that their programme offered”.…”
Section: Discussionmentioning
confidence: 99%
“…The provision of a risk quiz to the IWTK home collection programme was added to encourage participants to take a look at their own risk for having an STI, perhaps with gaining knowledge as to their own risk. Self-management of one's own reproductive health is becoming more popular; and improvement in the efficiency and delivery of sexual health care with a focus on innovation may popularise ‘Do it yourself’ sexual healthcare 17. Baraitser et al 18 have reported on the user experience for patients collecting their own samples, reporting that “clients were grateful for the service and preferred the autonomy, privacy and speed that their programme offered”.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Providing access to services for symptomatic individuals reduces the duration of infectiousness and screening high-risk asymptomatic individuals also decreases the duration of infectiousness. Our clinic has experienced increase demand in recent years with rising rates of chlamydia (Chlamydia trachomatis), gonorrhoea (Neisseria gonorrhoeae), syphilis and HIV.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several different strategies have been used to improve clinic efficiency and improve access to clinical services. 3 One of these was an express service for lower risk heterosexuals.…”
Section: Introductionmentioning
confidence: 99%
“…There has been considerable interest in the adoption of information and communication technology for prioritizing resources in sexually transmitted infections (STI) service delivery [1,2]. In British Columbia (BC), we are developing Get Checked Online (GCO), an Internet-based testing program that provides Web-based access to STI testing [3].…”
Section: Introductionmentioning
confidence: 99%